Visualization environment for reviewing and experimenting with compaction equipment trajectories in context. Issue 2 (April 2016) - Vasenev, A.; Hartmann, T.; Miller, S.R.; Dorée, A.G.
Graphical abstract: Highlights: Visualization Environments (VEs) usually aim either to review or simulate processes. Uniting both functionalities can support studying equipment trajectories in context. We suggest how to unite them within a VE for analyzing compaction processes. We developed an illustrative VE in consultation with asphalt paving professionals. Test results indicate that actual and demonstrated trajectories are commensurable. Abstract: Visualization Environments (VEs) can assist construction professionals in studying intricate interrelations between construction equipment trajectories and their context. Such VEs typically support them in either reviewing earlier conducted work or experimenting with possible alternatives. In the first case, VEs represent equipment trajectories and their actual context sensed during actual construction processes. Trying out alternative trajectories in such VEs is problematic. In the second case, environments support experimenting with alternative equipment trajectories within an a priori defined context, but demand significant modeling efforts to reconstruct real-world projects. Although combining both functionalities within a singular VE will enable obtaining benefits pertinent to each of the visualization environments classes, such attempts were not made earlier. To overcome this gap, this study proposes a method for developing interactive simulation visualization environments suitable for both reviewing conducted and experimenting with alternative equipment trajectories. The suggested method concentrates on compaction operations and comprises two steps: (1) application of a "context-actions-trajectory-impact" framework to structure interrelations between compaction equipment trajectories and their context; and (2) operationalization of an organization scheme to devise a specialized VE with the desired functionality. To evaluate the applicability of the proposed method we applied it for the case of the asphalt compaction process. We developed a specialized visualization environment in consultation with asphalt paving professionals. Two test sessions with a paving specialist and two professional roller operators were conducted with the developed VE. The results from the sessions show that the environment developed according to the method offers the envisioned functionality. As illustrated by the test results, original and demonstrated equipment trajectories are commensurable and able to provide meaningful insights into compaction operations.